Long-term lung perfusion changes related to COVID-19: a dual energy computed tomography study - Sonay Aydın; Erdal Karavaş; Edhem Ünver; Düzgün Can Şenbil; Mecit Kantarcı (Diagnostic and Interventional Radiology, 2023)

(untitled)
PURPOSEAlthough the findings of acute new coronavirus disease (COVID-19) infection on dual-energy computed tomography (DECT) have recently been defined, the long-term changes in lung perfusion associated with COVID-19 pneumonia have not yet been clarified. We aimed to examine the longterm course of lung perfusion in COVID-19 pneumonia cases using DECT and to compare changes in lung perfusion to clinical and laboratory findings.METHODSOn initial and follow-up DECT scans, the presence and extent of perfusion deficit (PD) and parenchymal changes were assessed. The associations between PD presence and laboratory parameters, initial DECT severity score, and symptoms were evaluated.RESULTSThe study population included 18 females and 26 males with an average age of 61.32 ± 11.3 years. Follow-up DECT examinations were performed after the mean of 83.12 ± 7.1 (80–94 days) days. PDs were detected on the follow-up DECT scans of 16 (36.3%) patients. These 16 patients also had ground-glass parenchymal lesions on the follow-up DECT scans. Patients with persistent lung PDs had significantly higher mean initial D-dimer, fibrinogen, and C-reactive protein values than patients without PDs. Patients with persistent PDs also had significantly higher rates of persistent symptoms.CONCLUSIONGround-glass opacities and lung PDs associated with COVID-19 pneumonia can persist for up to 80–90 days. Dual-energy computed tomography can be used to reveal long-term parenchymal and perfusion changes. Persistent PDs are commonly seen together with persistent COVID-19 symptoms.